Mathematical modelling of the osmotic dehydration of physalis - Assis, Fernanda Rosa (2018)
Physalis was osmotically dehydrated with 60 °Bx sucrose or sorbitol solutions at 60 °C and with a mass ratio of sample to solution of 1:4, at atmospheric pressure or under vacuum at 150 mbar. The Crank’s, Peleg’s and Page’s models were tested to describe the mass transfer kinetics for water loss (WL) and solids gain (SG). The effective diffusivities of both water and solute were around 10-11 m2 s-1 under all conditions. Peleg’s model presented the best fit. The use of sorbitol as the osmotic agent resulted in an increase in the WL rate. In experiments with sucrose solutions, a higher WL was obtained under vacuum than at atmospheric pressure. The SG was particularly low during osmotic dehydration. Thus, the use of sorbitol as the osmotic agent was shown to be a promising alternative to sucrose.